'More than a million': the politics of accounting for the dead of the Rwandan genocide. Issue 168 (3rd April 2021) - Reydams, Luc
ABSTRACT: Accounting for the dead after a humanitarian catastrophe is often fraught with methodological and/or political pitfalls. The genocide against the Tutsi in Rwanda is a case in point. A UN Commission of Experts estimated that between April and July 1994 at least 500, 000 civilians had been murdered. The post-genocide Rwandan government soon made clear that foreign help with demographic and forensic investigations was neither appreciated nor needed, and proceeded with its own counts of genocide victims. The article critically examines these counts; contrasts them with accounting efforts after the Bosnian conflict of the mid 1990s; compares the official Rwandan numbers with scholarly estimates; proposes an alternative method for calculating the death toll; and concludes that the official death toll roughly doubled the number of genocide victims. The article provides insight into how history is written in the new Rwanda.